Optimization Of Electrical Submersible Pump Size To Increase Dr-01 Well Production Rate Of Field Puyuh - Agustina Prihantini; Nurkhozin Adhi Nugroho; Dliya Ruhana (Jurnal Migasian, 2025)
Abstract. The "DR-01" well is installed with an electrical submersible pump with the problem of decreasing production and based on tests conducted on December 13, 2014 the production of the "DR-01" well produced 171 bfpd with a water content of 96%. The electrical submersible pump operates with the Allen C1000ARC pump type and pump setting depth of 4592 ft, TDH 4268.58 ft, number of stages 94, frequency 50 Hz, HP 28, head/stage 24 with a pump efficiency of 20%. In planning the optimization of a good and correct electrical submersible pump it will produce a pump efficiency value of above 35%. To overcome these problems, it is necessary to perform optimization calculations on electrical submersible pumps by calculating IPR values using the Wiggins method, calculating SGf and Gf values, calculating SBHP and FBHP values, calculating PIP, calculating TDH and pump performance curves. After optimizing the DR-01 well, the results obtained are the type of pump Allen C680AR, the pump setting depth value is 4653.92 ft, the total dynamic head value is 4202.74 ft, the number of stages is 145 stages, pump frequency is 60 Hz, Qgross value is 500 bfpd, horse power is 19 HP , head.stage 29, and a pump efficiency value of 57%. Where the value of the pump efficiency is considered optimum.